2017
DOI: 10.1002/2017jc012718
|View full text |Cite
|
Sign up to set email alerts
|

Modeling temperature inversion in southeastern Yellow Sea during winter 2016

Abstract: A significant temperature inversion with temperature differences larger than 3°C was observed in the southeastern Yellow Sea (YS) during February 2016. By analyzing in situ hydrographic profiles and results from a regional ocean model for the YS, this study examines the spatiotemporal evolution of the temperature inversion and its connection with wind‐induced currents in winter. Observations reveal that in winter, when the northwesterly wind prevails over the YS, the temperature inversion occurs largely at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Large inversions (ΔT ≥ 2.0°C) were observed in late February to March 1986 and in early April 1996. The large inversions have also been observed in February of 2003 and 2016 (Lie et al, 2015;Pang et al, 2017). Conversely, weak inversions with ΔT ≤ 0.5°C were observed in January 1986 and February 1997, despite temperature and salinity patterns (Figures 3 and 5) that demonstrate the formation of a strong frontal zone.…”
Section: 1029/2019jc015180mentioning
confidence: 86%
See 3 more Smart Citations
“…Large inversions (ΔT ≥ 2.0°C) were observed in late February to March 1986 and in early April 1996. The large inversions have also been observed in February of 2003 and 2016 (Lie et al, 2015;Pang et al, 2017). Conversely, weak inversions with ΔT ≤ 0.5°C were observed in January 1986 and February 1997, despite temperature and salinity patterns (Figures 3 and 5) that demonstrate the formation of a strong frontal zone.…”
Section: 1029/2019jc015180mentioning
confidence: 86%
“…The inversions northwest of Jeju‐do are not so significantly large as those southeast of the SP and the inversion area is apparently the smallest among the three frontal zones. However, large temperature differences in Δ T > 3.0°C were observed in February of 2003 and 2016 in that area (Lie et al, ; Pang et al, ). The relatively weak inversion there in January 1986 may be closely associated with the coarse spacing of CTD stations across the front between 33°N and 34°N, as CTD measurements were collected at stations with a north‐south distance of about 100 km.…”
Section: General Characteristics Of Temperature Inversion Layersmentioning
confidence: 96%
See 2 more Smart Citations
“…In winter, the Yellow Sea Warm Current (YSWC) has been widely studied because of its prominent hydrographic and upwind features (Hsueh, ; Huang et al, ; Lin & Yang, ; Tak et al, ). The YSWC significantly influences frontal circulation and the heat and water exchange in the Yellow Sea (Lie et al, , ; Pang et al, ), and its synoptic variation has been studied with numerical models in recent years (Ding et al, ; Hu et al, ; Li et al, ). These studies showed that after a strong northerly wind burst, a strong northward YSWC forms in the Yellow Sea trough and is associated with large‐scale SSH variations.…”
Section: Discussionmentioning
confidence: 99%